Food and non-food retail change in a post-communist country: A case study of the Gemer region in Slovakia - Bilková, Kristína; Križan, František; Horňák, Marcel; Barlík, Peter; Zubriczký, Gabriel (Bulletin of Geography. Socio-economic Series, 2018)
The retailing sector seems to be rather sensitive to social and economic developments in a society. In contrast to global retail network trends, specific processes may be observed in some lagging regions in post-communist countries. In the article attention is paid to spatial changes in food and non-food retailing locations in the region of Gemer, one of the least developed regions of post-communist Slovakia. The retailing network transformation between 1996 and 2012 was measured by applying retail capacity calculations for surplus or deficit, related to the population size of municipalities within the region. In the article, we examine food and non-food retail locations in the Gemer region with a special focus on spatial changes (urban vs rural) as well as temporal and trends based on retail capacity growth indices. In conclusion, the findings suggest that rural food and non-food retailing businesses have gone through considerable change and that it is not in harmony with the globalisation processes visible in the urban environment. Specifically, retail capacities (both food and nonfood) in the Gemer region are witnessing a period of growth.